Analisis Produktivitas Produksi Kerupuk Kulit Ikan Tuna UD. Putra Susila Menggunakan Objective Matrix (OMAX) - Simanjuntak, Debby Margareth; Satriawan, I Ketut; Harsojuwono, Bambang Admadi (Department of Agroindustrial Technology, Faculty of Agricultural Technology, Udayana University, 2025)
UD. Putra Susila tuna fish skin crackers specializes in producing tuna fish skin. In its activities, it is constrained by fluctuations in the supply of tuna fish skin raw materials which depend on the season, thus affecting overall productivity. The study aims to measure the value of productivity, analyze the value of cracker production ratio and develop recommendations for improving the value or target productivity of tuna fish skin crackers production at UD. Putra Susila from July to December 2023. The method used to measure company productivity is Objective Matrix (OMAX). There are 4 ratios that are adjusted to the company's conditions using efficiency criteria. The highest peak of the productivity value of tuna fish skin crackers production was in August 2023 with a productivity index value of 489.9%, the lowest value is in November 2023 at 175%. Analysis of the productivity ratio of tuna fish skin crackers gets the highest value in ratio 2 (the ratio of LPG gas usage costs to product value) at 495.64%, while the lowest productivity value was in ratio 4 (the ratio of the number of employees to product value) at 360.87%. Productivity improvement proposals that can be given are reducing employee working hours to 95 hours, saving LPG gas to Rp 4,130,429.76, optimizing raw materials to Rp 8,702,896.77, and maintaining the number of production employees as many as 7 people